Termitomyces di Kawasan Urban Kecamatan Gunungpati, Kota Semarang, Jawa Tengah - Ferry Augustinus; Ivan Permana Putra (Buletin Plasma Nutfah, 2021)
Termitomyces is a popular wild edible mushroom in paleotropic region including Indonesia. This mushroom is commonly harvested by people around rural area in Indonesia while foraging for food alternative. However, the information regarding Termitomyces usage in urban area is very limited. The objective of this current study is to provide preliminary information about diversity and biological characters of Termitomyces from city forest in Gunungpati, Semarang City, Central Java. Mushroom exploration is done by opportunistic sampling method and identification was carried out by macroscopic observation of morphological characteristics. A total of  7 species of Termitomyces were found  in this study. They were Termitomyces cf. medius, Termitomyces cf. globulus 1, Termitomyces cf. globulus 2 Termitomyces cf. bulborhizus, Termitomyces cf. microcarpus, Termitomyces cf. clypeatus, and Termitomyces cf. eurhizus.  This study is the first report of Termitomyces inventory in the research site and contributing to Indonesia's diversity data.